Effective Microorganisms Improve Growth, Nutrients Uptake, Normalized Difference Vegetation Index, Photosystem II, and Essential Oil While Reducing Canopy Temperature in Water-Stressed Salvia sclarea Plants - Naayem M. Elgaml; Adel B. Salama; Heba Sh. Shehata; Magdi T. Abdelhamid (International Journal of Agronomy)
Clary sage (Salvia sclarea L.), a member of the Lamiaceae family of aromatic plants, is used as a flavoring in the food, fragrance, and cosmetic industries. Egypt’s food and pharmaceutical industries require more natural resources, thus new crops have been introduced to meet the demand. In addition, various environmental conditions, such as water stress, influence aromatic plant growth and essential oil output. The microorganisms included in biofertilizers that have enzymes that solubilize minerals include plant growth-promoting rhizobacteria (PGPRs). Therefore, a field experiment was carried out to test how irrigation management, i.e., 100% of reference evapotranspiration (ETo) (full irrigation) or 50% ETo (water stress), can affect herbal yield, essential oil, and physiological aspects of clary sage, as well as how to improve clary sage plants utilizing biofertilizer in the field in Egypt’s Mediterranean climate zone. The main processes through which PGPRs aid clary sage plants in coping with water stress include increased macro and micronutrient concentrations (P, N, K, Ca, Mg, Zn, B, Mn, Cu, and Fe), dehydrogenase activity, essential oil, and physiological and growth traits of photosystem II (Fv/Fm), chlorophyll content (SPAD-value), plant’s health (normalized difference vegetation index, NDVI), shoot dry weight, and leaf area in clary plants. Application of different PGPRs reduced canopy temperature (CT), thus improving clary sage plants either under 100% ETo or 50% ETo. Consequently, the usage of PGPRs is appropriate for alleviating environmental stresses experienced by clary sage plants and has potential use in maintaining productivity in water stress and may thus be regarded as an important component of sustainable agricultural practices.